Purification and Characterization of a Novel Calcium-Binding Heptapeptide from the Hydrolysate of Tilapia Bone with Its Osteogenic Activity - He, Jinlun; Guo, Hao; Zhang, Mei; Wang, Meng; Sun, Liping; Zhuang, Yongliang (Foods, 2022)
In this study, a calcium-binding peptide was obtained by hydrolyzing tilapia bone and its osteogenic activity was evaluated. Animal protease was selected from nine enzymes, and its hydrolysate was purified through preparative and semi-preparative reverse phase high-performance liquid chromatography. The purified peptide was identified as DGPSGPK (656.32 Da) and its calcium-binding capacity reached 111.98 µg/mg. The peptide calcium chelate (DGPSGPK-Ca) was obtained, and its structure was characterized through Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and mass spectrometry (MS). The results of XRD and SEM showed that DGPSGPK-Ca was formed as a new compound. The carboxyl and amino groups of Lys and Asp residues may be the chelating sites of DGPSGPK according to the FTIR and MS results. The molecular simulation showed the carbonyl groups of Asp, Pro, Ser, and Lys residues involved in the binding of calcium. The interaction of DGPSGPK and different integrins was evaluated by molecular docking simulation, and the main forces involved were electrostatic interaction forces, hydrogen bonding and hydrophobic interactions. Furthermore, DGPSGPK could inhibit the differentiation of osteoclast and promote the proliferation, differentiation and mineralization of osteoblasts.